Clinical nursing experiences in Singapore: A far away from home - Astuti, Wiji (Universitas Muhammadiyah Magelang, 2023)
As the global population lives longer, healthcare systems must adapt to meet new problems. The seamless transition of patients from acute care settings to home environments is now possible thanks to the implementation of transitional care teams. It may be said that nurses' duties have 'emerged differently' than their conventional counterparts. To better support care integration, various nurse duties have been taken on. This article presents a clinical experience that was gained while working in a nursing home in Singapore. When working in a foreign country, nurses should be well prepared, both in terms of their knowledge and their professional skills. Keywords: Healthcare system; working abroad; community health; innovation in society; clinical experiences